From Local Products to Competitive Advantage: Stakeholder Roles in Alcoholic Beverage Branding in Bali’s Hospitality Industry - Ni Luh Putu Agustini Karta; Stephanus Remond Waworuntu; Ni Made Ary Widiastini; Isauro Sorongon Sindol Jr. (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
Balinese Arak (an alcoholic beverage) faces structural challenges in governance, market positioning, and brand consolidation despite legalization under Bali Governor Regulation No. 1 of 2020 and production exceeding 4,000 liters per month. Fragmented pricing, inconsistent quality, and weak brand governance limit its competitiveness in Bali’s hospitality industry, dominated by imported wines and international spirits. This study examines how stakeholder collaboration and governance mechanisms strengthen branding and competitive positioning of Balinese Arak as a heritage-based tourism product. Using a qualitative approach through in-depth interviews and focus group discussions with artisans, cooperatives, government officials, and hospitality actors in Karangasem Regency (a key production center) in East Bali, the findings reveal that regulatory support, cooperative institutionalization, product standardization, and collaborative branding convert cultural legitimacy into competitive advantage. Branding functions as a governance-driven process integrating quality assurance, adaptive innovation, and cross-sector collaboration, enhancing market credibility, hospitality integration, and long-term sustainability within Bali’s tourism economy.